Shorting in Speculative Markets - NUTZ, MARCEL; SCHEINKMAN, JOSÉ A. (Journal of Finance, 2020)
ABSTRACT In models of trading with heterogeneous beliefs following Harrison‐Kreps, short selling is prohibited and agents face constant marginal costs‐of‐carry. The resale option guarantees that prices exceed buy‐and‐hold prices and the difference is identified as a bubble. We propose a model where risk‐neutral agents face asymmetric increasing marginal costs on long and short positions. Here, agents also value an option to delay, and a Hamilton‐Jacobi‐Bellman equation quantifies the influence of costs on prices. An unexpected decrease in shorting costs may deflate a bubble, linking financial innovations that facilitated shorting of mortgage‐backed securities to the collapse of prices.